Enhanced RC5 Algorithm using Parallel Computing for Communication Networks (2019)
One of the main disadvantages of symmetric key algorithms in comparison with asymmetric key ones is their lower security level due to their shorter key length. Indeed, increasing the number of bits that conforms the key used by a symmetric cryptography algorithm will increase its security level with a cost on its performance. Expanding a key in symmetric cryptography is not an easy task due to algorithms are designed to work with keys of a fixed maximum length. This paper presents an alternative design of the RC5 cryptography algorithm with an enhanced security level achieved through a key expansion mechanism with Parallel Computing processing. Although the design was created for the RC5 algorithm the main idea might be applied to other block cipher algorithms applying the same criteria. This methodology makes feasible to obtain a robust symmetric key algorithm implemented in software with an acceptable performance in comparison with other techniques such as implementations in hardware, reduction in the amount of data, improvements in the key exchange process, advanced high performance computing, and many others techniques.